Soil properties of the permafrost zone and differences among regions of Mongolia - Tserengunsen, Purevdorj; Turmunkh, Telmen; Avirmed, Dashtseren; Khurelbaatar, Temuujin; Ochirjav, Tuvshintur (Institute of Geography and Geoecology, Mongolian Academy of Sciences, 2022)
The distribution of permafrost in Mongolia is sporadic and discontinuous depending on the location, landscape, and temperature. Also, the characteristics and patterns of its soil cover vary across the regions. In this study, we aimed to determine the characteristics of the soil cover distributed in the permafrost regions and differences across the regions of Mongolia. We divided the studied permafrost regions into Mongolian-Altai, Gobi-Altai, Khangai, and Khuvsgul, and collected 164 soil samples at fixed depths of 0-5 cm, 5-15 cm, 15-30 cm, and 30-60 cm in 41 soil profiles around permafrost monitoring boreholes. As the result, Kastanozems and Chernozems soils were dominated in the Khuvsgul and Khangai while Aridic Kastanozems soils were more prevalent in Mongolian-Altai and Gobi-Altai. The soil pH was from neutral to slightly alkaline, and the carbonate content was from low to moderate. The soil organic matter, available phosphorus, and potassium decreased with the depth of the soil profile. Soil texture was distributed evenly, and the content of gravel was in the order of Gobi-Altai, Mongolian-Altai, Khangai, and Khuvsgul. Considering soil organic carbon, at 0-60 cm, it was 4.2 kg m-2 in Mongolian-Altai, 3.0 kg m-2 in Gobi-Altai, 6.8 kg m-2 in Khangai, and 7.5 kg m-2 in Khuvsgul. Монгол орны цэвдэгт газрын хөрсний шинж чанар, бүс нутгийн ялгаа ХУРААНГУЙ Манай орны цэвдэг нь газарзүйн байрлал, ландшафт, температураас хамааран бүс нутаг бүрд адилгүй тасалданги, алаг цоог хэлбэртэйгээр тархсан. Үүнийгээ дагаад хөрсний шинж чанар, хэв шинж нь ялгаатай байдаг. Бид энэ судалгааг Монгол орны цэвдэгт бүс нутагт тархсан хөрсний шинж чанарыг тогтоох, бүс нутгийн хувьд ямар нэгэн ялгаа байгаа эсэхийг илрүүлэх зорилготой хийлээ. Ингэхдээ судалгааны талбайг Хангай, Хөвсгөл, Монгол-Алтай, Говь-Алтай гэж хуваан цэвдгийн цооногуудын ойролцоо 41 (30 нь цэвдэгтэй, 11 нь цэвдэггүй) хөрсний зүсэлт хийн 0-5 см, 5-15 см, 15-30 см, 30-60 см гэсэн тогтмол гүнүүдээс 164 ширхэг хөрсний дээж аван тодорхойлсон. Судалгааны үр дүнгээс ...